1980
DOI: 10.1038/bjc.1980.221
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of malignant disease in childhood: a 24-year review of the Manchester Children's Tumour Registry data

Abstract: The Manchester Children's Tumour Registry data for the period 1954-1977 have been analysed. The overall incidence of malignant disease in children aged 0-14 years in the north-west of England is estimated to be 100 per million person-years. The most common disease group is leukaemia, which forms about one third of the total number of cases. Among solid tumours, by far the most common presenting site is the central nervous system, representing nearly a quarter of all neoplasms. Wilms' tumour, neuroblastoma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0
3

Year Published

1981
1981
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 9 publications
3
44
0
3
Order By: Relevance
“…The paucity of data on childhood cancer incidence in different parts of the world has already been pointed out (Birch et al, 1980) and it is hoped that publication of data such as ours will lead to the establishment of other specialized childTotal 40 0 2-9 11-4 2-9 40 0 2-9 100 0 100-0 hood-cancer registries. Childhood cancer comprises only about 1% of all cancers, and it is therefore not surprising that very few general cancer registries have made special studies of the incidence of childhood cancer within their regions.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The paucity of data on childhood cancer incidence in different parts of the world has already been pointed out (Birch et al, 1980) and it is hoped that publication of data such as ours will lead to the establishment of other specialized childTotal 40 0 2-9 11-4 2-9 40 0 2-9 100 0 100-0 hood-cancer registries. Childhood cancer comprises only about 1% of all cancers, and it is therefore not surprising that very few general cancer registries have made special studies of the incidence of childhood cancer within their regions.…”
Section: Resultsmentioning
confidence: 86%
“…the incidence of childhood cancer throughout the world, and most of these are from cool or temperate areas of the northern hemisphere (Young & Miller, 1975;Ericsson et al, 1978;Teppo et al, 1975;Birch et al, 1980;Pastore et al, 1979). Data from most cancer registries about childhood cancer are not sufficiently detailed, and therefore of limited value.…”
mentioning
confidence: 99%
“…Birch JM et al [15] found that among all the malignant diseases in childhood, one third of the cases were leukemia and it was the most common malignant disease in children in their series. Pradhan P et al [8] found that among children, Acute leukemias were more common (97.3%) and Chronic leukemias were only 2.7% of all cases.…”
Section: Discussionmentioning
confidence: 96%
“…The national leukaemia morbidity registry of the DCLSG meets all three criteria mentioned by Young & Miller (1975) (Birch et al, 1980). Higher total leukaemia incidence rates were observed in Australia, Finland, Sweden and the U.S.A.…”
Section: Discussionmentioning
confidence: 98%
“…In all studies ALL is the most common type of leukaemia in childhood. In the Manchester region (Birch et al, 1980) and in the Netherlands it accounts for 79% and 82.4% respectively.…”
Section: Discussionmentioning
confidence: 99%